(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article analyzes the role of the family as a social institution in society and its position as a socio-cultural mechanism of upbringing. The author draws attention to the structural complexity of the family, the role of the mother in upbringing in particular, and the continuity of national values. The formation of such aspects of upbringing as labor, morality, spirituality, patriotism in the family environment is substantiated. The article also covers the role of family upbringing in state policy, the process of passing values ​​from generation to generation, and the issues of upbringing based on national pedagogical traditions.